Ammonium hydroxide modification of polylactic acid and polyglycolic acid monofilaments for acupoint catgut embedding therapy. Issue 17 (September 2020) - Fu, Shaoju; Lu, Yao; Zhang, Peihua
Polylactic acid (PLA) and polyglycolic acid (PGA) monofilaments have attracted much attention for their wide usage in acupoint catgut embedding therapy (ACET). Their application is restricted, however, by their poor hydrophilicity and cell attachment properties. In this study, PLA and PGA monofilaments were produced from polymer chips, and then modified by the application of an ammonium hydroxide solution to the surface. The modified PLA and PGA monofilaments were fully characterized with respect to their structural, mechanical, and in-vitro properties. The results showed that the surface roughness and hydrophilicity of the materials were greatly increased; surface modified samples of both materials exhibited the smallest contact angle values: 79.2° ± 2.5° (sample PLA2) and 75.9° ± 1.4° (sample PGA2). The weights and diameters and the tensile and flexibility properties of the materials changed little with surface modification, but their swelling ratios increased significantly. All the prepared samples were non-toxic (more than 75% of cells being viable). Surface modification also enhanced cell attachment: PLA2 (48.15% ± 2.16%) and PGA2 (59.43% ± 3.18%) showed the largest cell attachment values (cultured for 48 h) among the samples. In summary, the study proves the feasibility of ammonium hydroxide modification of PLA and PGA, which is beneficial for guiding future work on developing functional PLA or PGA materials for ACET.